Anti-collapse automobile interior real leather and real leather seat structure
By adopting a composite structure of leather layer, hot melt film layer and mesh cloth layer in leather seats, combined with vegetable-tanned leather technology with high bio-based carbon content, the problem of collapse and throwing of leather seats is solved, and the softness is maintained and tear performance, and reduce carbon emissions and improve mechanical properties.
Patent Information
- Application Number
- CN202411540978.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-14
AI Technical Summary
Leather seats are prone to collapse and throwing problems during use, and the prior art loses the softness and tearing properties of the leather when trying to solve it.
Using a composite structure consisting of a leather layer, a hot melt adhesive film layer and a mesh cloth layer, the transverse and longitudinal elongations of the mesh cloth layer are different. Through the composite of the hot melt adhesive film layer and the leather layer, it combines with a high bio-based carbon content. Vegetable tanned leather process, prepare anti-collapse genuine leather for automotive interiors, and add leather composite sponge and zero gravity filling layer to the leather seats.
It effectively prevents the collapse and throwing of leather seats, maintains the softness and tear performance of leather, while reducing carbon emissions, improving the mechanical properties and bio-based carbon content of leather.
Smart Images

Figure CN119305262A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of leather, and in particular to an anti-collapse automobile interior genuine leather and a genuine leather seat structure. Background Art
[0002] The reason why leather seats are becoming more and more popular is mainly due to their unique advantages. First of all, leather has natural breathability and moisture absorption, which can effectively keep the seat surface dry and comfortable, and avoid the stuffiness and humidity caused by long-term driving. Secondly, leather seats are soft and delicate to the touch, which can enhance the riding experience of drivers and passengers. In addition, leather seats are also wear-resistant, dirt-resistant, and easy to clean, making them more durable and convenient in daily use. At the same time, leather seats have become a necessity for luxurious interiors in the hearts of Chinese people, and leather seats have become the first choice for more and more car models to improve customer perception.
[0003] With the rapid development of the automobile industry, consumers are becoming more and more demanding on car interiors. Leather seats, due to their noble and elegant texture and good touch, have gradually become the first choice for the interiors of many models. However, with the popularity of leather seats, the problems of collapse and air drop have gradually come into people's view.
[0004] This study will analyze the collapse phenomenon of leather seats and its causes. On the one hand, as a natural material, leather has a certain degree of elasticity and flexibility, and the performance of leather varies greatly in all directions. During use, due to the weight of the human body and frequent movement, the surface of the leather seat is prone to creases and deformation. On the other hand, domestic car seat design pursues more comfort, using multiple layers of soft sponge to improve the sofa feel of the seat surface.
[0005] The current solution to solve the wrinkles on the seat cover and the seat's durability is to reduce the softness of the single leather BLC by 0.5-1.0 or to compound the leather back with conventional KUFNER, which will make the leather surface hard and lose the comfort of the seat. According to this solution of the prior art, the bio-based leather produced loses the original leather's feel and tearing performance.
[0006] In summary, in order to solve the problems of the prior art, the present invention provides an anti-collapse automobile interior leather and leather seat structure. Summary of the invention
[0007] The purpose of the present invention is to provide an anti-collapse automobile interior genuine leather, which can not only lose softness as little as possible, but also prevent covering wrinkles and seat throwing.
[0008] To achieve the above purpose, the following technical solutions are used:
[0009] An anti-collapse automobile interior genuine leather, the anti-collapse automobile interior genuine leather 10 comprises:
[0010] Leather layer 11;
[0011] Hot melt adhesive film layer 12;
[0012] Mesh cloth layer 13;
[0013] in,
[0014] The mesh cloth layer 13 is a knitted fabric, the transverse elongation of the mesh cloth layer 13 is a, and the longitudinal elongation of the mesh cloth layer 13 is b, satisfying the quantitative relationship: a≠b.
[0015] As a further improvement, the mesh fabric layer 13 is CV&PESF, ie, cotton / bio-based elastic polyester fiber.
[0016] In this embodiment, by compounding the mesh cloth layer 13 on the flesh side of the leather of the leather layer 11 through the hot melt adhesive film layer 12, and then setting the mesh cloth layer 13 to have different elongation rates in the transverse and longitudinal directions, the elongation performance and deformation rate of the leather fibers can be effectively constrained.
[0017] As a further improvement, the hot melt adhesive coating amount of the hot melt adhesive film layer 12 is 23±2 / g.
[0018] As a further improvement, the thickness of the leather layer 11 is 1.2±2 mm.
[0019] As a further improvement, through holes are provided on the leather layer 11 , the diameter of the through holes is 1.0 mm, and the hole spacing is 4*4 mm.
[0020] As a further improvement, the leather layer 11 is a car interior vegetable tanned leather with a high bio-based carbon content.
[0021] As a further improvement, the method for preparing the high bio-based carbon content automotive interior vegetable tanned leather comprises the following preparation steps:
[0022] Step 1: Water field process;
[0023] Step 2: coating process;
[0024] in,
[0025] The water yard process includes: fur feeding, soaking, liming, splitting, deliming, pickling, tanning, retanning, dyeing, fatliquoring and finishing;
[0026] The coating process includes: base coating, surface coating, and top coating;
[0027] It is characterized in that
[0028] The biomass material CoralonNL Liquire is used in the fur to white leather stage, and the biomass material accounts for 10 to 30 parts by weight;
[0029] Biomass materials are used in the tanning stage, and the biomass materials account for 80 to 100 parts by weight;
[0030] Biomass materials are used in the retanning stage, and the biomass materials account for 40 to 60 parts by weight;
[0031] Biomass materials are used in the dyeing stage, and the weight proportion of the biomass materials is 0 to 10 parts;
[0032] Biomass materials are used in the fatliquoring stage, and the biomass materials account for 20 to 70 parts by weight;
[0033] Biomass materials are used in the coating stage, and the biomass materials account for 30 to 60 parts by weight.
[0034] A leather seat structure, comprising:
[0035] Anti-slump car interior genuine leather 10;
[0036] Leather composite layer sponge 20;
[0037] Zero gravity fill layer 30.
[0038] As a further improvement, the compressive strength of the zero-gravity filling layer 30 is 6.5±2.5 / Kpa.
[0039] As a further improvement, the thickness of the leather composite layer sponge 20 is 8-10 mm.
[0040] As a further improvement, the thickness of the zero-gravity filling layer 30 is 10-15 mm.
[0041] The anti-collapse genuine leather for automobile interior decoration of the present invention has the following beneficial effects:
[0042] 1) The anti-collapse automobile interior genuine leather, by specifically selecting a mesh cloth layer, and compounding the mesh cloth layer with the leather layer 11 through hot melt adhesive, the obtained leather has the lowest elongation under fixed load and residual deformation rate, and the highest BLC softness value, indicating that the elongation under fixed load and residual deformation rate can be effectively reduced by compounding with the mesh cloth layer, while the softness of the genuine leather is not lost;
[0043] 2) The mesh cloth layer in the anti-collapse automobile interior genuine leather uses a knitted fabric of CV&PESF, which has different elongation rates in the horizontal and vertical directions. By sticking the adhesive film on the flesh surface of the genuine leather, the elongation performance and deformation rate of the genuine leather fiber can be effectively restricted, thereby effectively preventing collapse.
[0044] The high bio-based carbon content vegetable tanned leather for automobile interior decoration of the present invention has the following beneficial effects:
[0045] 3) In each stage of using chemical materials, this method gives priority to using chemical materials synthesized from biomass materials, which not only does not affect the quality and performance of leather (biobased carbon content ≥ 85%), but also effectively reduces carbon emissions (compared with traditional leather, carbon emissions are reduced by 2.0KG / m 2 );
[0046] 2) By adding chemicals synthesized from biomass materials in the leather liming workshop, tanning, retanning, greasing and finishing stages, the leather produced can have both better mechanical properties (tensile strength ≥120 (N), tear force ≥23.00 (N), stitching fatigue strength ≤2mm, friction color fastness ≥4, abrasion ≥4 levels) and higher bio-based carbon content (bio-based carbon content ≥85%). BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 It is a plan view of the leather;
[0048] Figure 2 Schematic diagram of the structure of genuine leather for car interior to prevent collapse;
[0049] Figure 3 It is a structural diagram of the leather seat structure;
[0050] Figure 4 It is the test sample Ⅰ in Example 2;
[0051] Figure 5 It is the test sample II in Example 2;
[0052] Figure 6 This is the test sample III in Example 2.
[0053] Figure 7 This is a schematic diagram of the process flow of producing vegetable tanned leather for automotive interior decoration with high bio-based carbon content according to the present invention;
[0054] Figure 8 This is a schematic diagram of the structure of the vegetable tanned leather for automotive interior decoration with high bio-based carbon content of the present invention; DETAILED DESCRIPTION
[0055] In order to make the purpose, technical solutions and advantages of the present invention more clear, the following embodiments and the accompanying drawings are combined to illustrate the present invention. Figures 1 to 8 The present invention will be further described:
[0056] Example 1
[0057] An anti-collapse automobile interior genuine leather, the anti-collapse automobile interior genuine leather 10 comprises:
[0058] Leather layer 11;
[0059] Hot melt adhesive film layer 12;
[0060] Mesh cloth layer 13;
[0061] in,
[0062] The mesh cloth layer 13 is a knitted fabric, the transverse elongation of the mesh cloth layer 13 is a, and the longitudinal elongation of the mesh cloth layer 13 is b, satisfying the quantitative relationship: a≠b.
[0063] In this embodiment, by compounding the mesh cloth layer 13 on the flesh side of the leather of the leather layer 11 through the hot melt adhesive film layer 12, and then setting the mesh cloth layer 13 to have different elongation rates in the transverse and longitudinal directions, the elongation performance and deformation rate of the leather fibers can be effectively constrained.
[0064] More preferably: the hot melt adhesive coating amount of the hot melt adhesive film layer 12 is 23±2 / g; the thickness of the leather layer 11 is 1.2±2mm; the leather layer 11 is provided with through holes, the aperture of the through holes is 1.0mm, and the hole spacing is 4*4mm.
[0065] Example 2
[0066] like Figure 1 As shown, Figure 1 This is a plane view of the leather. The direction from the buttocks to the neck is the L direction, and the direction perpendicular to the L direction is the W direction. Usually, the constant load elongation and residual deformation rate of the leather in the W direction are relatively large, especially in the abdomen of the cow No. 5, the constant load elongation and residual deformation rate are even larger.
[0067] Three samples were taken from the standard part of the leather, each with a BLC softness of about 3.6. Holes were punched according to the hole diameter of 1.0mm and the hole spacing of 4*4. After punching, they were thermally compounded with mesh cloths Ⅰ#, Ⅱ#, and Ⅲ# respectively. After compounding, the fixed load elongation, residual deformation rate and BLC softness of the three samples were tested.
[0068] The mesh fabric layer 13 is CV&PESF, i.e. cotton / bio-based elastic polyester fiber.
[0069] The technical parameters of Ⅰ# mesh cloth are:
[0070] Structure: Knitted fabric
[0071] Composition: 68% CV, 32% PESF
[0072] Coating: PA double dot, 14 mesh (44 dots / cm2)
[0073] Weight: Total 58±5g / m 2
[0074] Coating weight: 15±2g / m 2
[0075] Thickness: 0.40±0.10mm
[0076] Tensile strength: >80N / 5cm
[0077] Elongation under maximum force: bending direction>18%, wrapping direction%>8%
[0078] The technical parameters of Ⅱ# mesh cloth are:
[0079] Structure: Knitted fabric
[0080] Composition: 74% CV, 26% PESF
[0081] Coating: PA double dot, 17 mesh (52 dots / cm2)
[0082] Weight: Total 65±5g / m 2
[0083] Coating weight: 15±2g / m 2
[0084] Thickness: 0.40±0.10mm
[0085] Tensile strength: >80N / 5cm
[0086] Elongation under maximum force: bending direction>15%, wrapping direction%>6%
[0087] The technical parameters of III# mesh cloth are:
[0088] Structure: Knitted fabric
[0089] Composition: 64% CV, 36% PESF
[0090] Coating: PA double dot, 12 mesh (42 dots / cm2)
[0091] Weight: Total 55±5g / m 2
[0092] Coating weight: 15±2g / m 2
[0093] Thickness: 0.40±0.10mm
[0094] Tensile strength: >80N / 5cm
[0095] Elongation under maximum force: bending direction>20%, wrapping direction%>9%
[0096] The specific test results are shown in Table 1.1.
[0097] Table 1.2
[0098]
[0099] From the test results in Table 1.2, it can be seen that the elongation under fixed load and the residual deformation rate of sample II are the lowest, and the BLC softness value of sample II is the highest, which means that the use of II# mesh cloth can effectively reduce the elongation under fixed load and the residual deformation rate, while taking into account the softness of the leather.
[0100] Example 3
[0101] A leather seat structure, comprising:
[0102] Anti-slump car interior genuine leather 10;
[0103] Leather composite layer sponge 20;
[0104] Zero gravity filling layer 30, zero gravity filling layer 30 is polyether\sponge density 40±4 / kg·m -3 \Compression strength 6.5±2.5 / Kpa.
[0105] As a further improvement, the zero gravity filling layer 30 is a polyether sponge with a density of 40±4 / kg·m -3 The compressive strength of the zero-gravity filling layer 30 is 6.5±2.5 / Kpa.
[0106] More preferably, the leather composite sponge 20 has a thickness of 8 to 10 mm, and the zero-gravity filling layer 30 has a thickness of 10 to 15 mm.
[0107] The present leather seat structure can not only effectively solve the problems of seat covering wrinkles and seat durability, but also take into account the softness of the leather surface without losing the comfort of the seat.
[0108] Example 4
[0109] The current manufacturing process of bio-based leather usually includes two key steps: raw material extraction and processing. Raw material extraction refers to the extraction of the desired compounds or fibers from biomass. These raw materials can be obtained through biomass conversion, fermentation, extraction and other methods. Processing refers to the processing and improvement of the extracted materials to obtain materials with the desired properties. The processing method is usually to make genuine leather into fibers, and then spin, needle punch and surface coat with biomass materials.
[0110] The bio-based leather produced according to this solution of the prior art loses the hand feel and tearing properties of the original leather.
[0111] The present invention extracts the required compounds from biomass and processes these biomass compounds into chemical materials required for leather making, such as tanning, retanning agents, fatliquor, adhesive resin, primer resin, top-coating resin, cross-linking agent, etc. Then, these biomass materials are applied to the liming, tanning, retanning, fatliquor and finishing of genuine leather, thus reducing the environmental footprint without affecting the quality and performance of leather.
[0112] The leather layer 11 is a car interior vegetable tanned leather with a high bio-based carbon content;
[0113] The method for preparing the vegetable tanned leather for automobile interior with high bio-based carbon content comprises the following preparation steps:
[0114] Step 1: Water field process;
[0115] Step 2: coating process;
[0116] in,
[0117] The water yard process includes: fur feeding, soaking, liming, splitting, deliming, pickling, tanning, retanning, dyeing, fatliquoring and finishing;
[0118] The coating process includes: base coating, surface coating, and top coating;
[0119] It is characterized in that
[0120] BEAM-HOUSE fur to white fur stage uses biomass material Coralon NL Liquire, and the biomass material accounts for 10 to 30 parts by weight;
[0121] The biomass material Granofin TA & Synektan GA is used in the tanning stage, and the biomass material accounts for 80 to 100 parts by weight;
[0122] The biomass material TanicorFO is used in the retanning stage, and the biomass material accounts for 40 to 60 parts by weight;
[0123] The biomass material Lipoderm Eco AS is used in the dyeing stage, and the biomass material accounts for 0 to 10 parts by weight;
[0124] The biomass material Derminol PUA is used in the fatliquoring stage, and the biomass material accounts for 20 to 70 parts by weight;
[0125] The biomass materials Eukesol Oil Ground & WT-66-486 & XR-66-585 are used in the coating stage, and the biomass materials account for 30 to 60 parts by weight.
[0126] In the stage of BEAM-HOUSE fur to white fur, soaking agents, preservatives, degreasing agents, acidifying agents, and enzyme preparations are used;
[0127] During the tanning stage, various tanning agents are used to denature the dermal collagen, thereby making the acid and alkali resistance of the dermis more stable. Common tanning agents include chromium powder, glutaraldehyde, plant tannin, zeolite tanning agent, etc.
[0128] In the retanning and dyeing stage, various acrylic retanning agents, phenolic retanning agents, sulfone retanning agents, phenolic retanning agents, sulfite fish oil, sulfite castor oil, neat's foot oil, lecithin, fish oil, organic dyes, inorganic dyes, etc. are used.
[0129] Therefore, in the present invention, at each stage of using chemical materials, chemical materials synthesized from biomass materials are preferably used, such as using bio-based additives in the liming and deliming processes to accelerate liming and deliming;
[0130] In the tanning stage, vegetable tannin extracted from plants is used as the main tanning agent;
[0131] Neutralizers, retanning agents, fillers and fatliquors using biomass in the retanning stage;
[0132] Biomass resins and biomass cross-linkers are used in the finishing stage.
[0133] In the preparation method of the vegetable tanned leather for automobile interior with high bio-based carbon content, the biomass material is reasonably and effectively applied to the leather making process, and the mechanical properties, friction resistance and abrasion resistance of the leather for automobile interior can also be taken into account.
[0134] Through the following process design and verification process, we can finally obtain automotive interior vegetable tanned leather with high bio-based carbon content, while taking into account the mechanical properties, friction resistance and abrasion resistance of automotive interior leather.
[0135] Firstly, the entire process does not use biomass materials, only traditional fossil-based materials.
[0136] The specific formula is shown in Table 2.1.
[0137] Table 2.1
[0138]
[0139]
[0140] The finished leathers after tanning, retanning and finishing with the materials in Table 1.1 were tested for bio-based carbon content using ASTM D6866-22 Method B (AMS) TOC. The test result showed that the bio-based carbon content was 74%. This result shows that the 74% bio-based carbon is entirely derived from the raw cowhide, and the chemical materials used in the later processing contribute 0% to the bio-based content of the finished leather.
[0141] By selecting different amounts of biomass materials in different processes, the bio-based carbon content of the finished leather is tested. The specific design plan is shown in Table 2.2.
[0142] Table 2.2
[0143]
[0144] The bio-based carbon content of the finished leather after tanning, retanning and finishing using the materials in Table 2.2 was tested using ASTM D6866-22 Method B (AMS) TOC. The test results are shown in Table 1.3.
[0145] Table 2.3
[0146]
[0147] It can be seen from Table 2.3 that when biomass additives accounting for 30% of the total chemical materials are used in the beam-house stage, the bio-based carbon content of the finished leather is 75%, and the bio-based carbon content increases by 1%; when biomass tanning agents are used entirely in the tanning stage, the bio-based carbon content of the finished leather is 80%, and the bio-based carbon content increases by 5%; when biomass retanning agents accounting for 60% of the total chemical materials are used in the retanning stage, the bio-based carbon content of the finished leather is 77%, and the bio-based carbon content increases by 2%; when biomass fatliquors accounting for 70% of the total chemical materials are used in the fatliquor stage, the bio-based carbon content of the finished leather is 78%, and the bio-based carbon content increases by 3%; when biomass resins and cross-linking agents accounting for 60% of the total chemical materials are used in the finishing stage, the bio-based carbon content of the finished leather is 76%, and the bio-based carbon content increases by 2%; in the whole process, each process selects the largest proportion of biomass materials, and the final bio-based carbon content of the finished leather is 89%, and the bio-based carbon content increases by 15%.
[0148] It can be seen that the biobased content of sample F is the highest at 89%. Sample F was tested at the same time, and the test results are shown in Table 2.4.
[0149] Table 2.4
[0150]
[0151] From the test results in Table 2.4, it can be seen that the tearing performance and suture fatigue strength tests in the mechanical properties failed, and the wear resistance test of the coating failed; the reason for the failure of the mechanical properties is that the performance of the fatliquor in the fatliquor process did not exert the tearing resistance, and the reason for the failure of the wear resistance of the coating is that the wear resistance of the top light resin is not good, because the mechanical properties are directly related to the performance of the fatliquor, the higher the biomass content, the more it affects the tearing performance. Similarly, the friction color fastness and wear performance of the coating are directly related to the amount of biomass material used in the layer. The more the amount, the worse the performance, so the amount is changed from more to less, and it is verified again.
[0152] In order to improve the above two test items and ensure that the bio-based carbon content in the leather is ≥85%, the test plan is designed as shown in Table 2.5.
[0153] Table 2.5
[0154]
[0155] The mechanical properties and coating properties of samples Ⅰ, Ⅱ and Ⅲ were tested on the finished leathers after tanning, retanning and finishing using the materials in Table 2.5. The test results are shown in Table 2.6.
[0156] Table 2.6
[0157]
[0158] From the test results in Table 2.6, it can be seen that the mechanical properties and coating properties of sample III can meet the requirements of automotive interior leather. The greasing process uses a biomass greasing agent that accounts for 20% of the total chemical materials, and the coating stage uses a biomass resin and cross-linking agent that accounts for 30% of the total chemical materials.
[0159] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent changes made using the present invention are within the patent protection scope of the present invention.
Claims
1. An anti-collapse genuine leather for automobile interior, characterized in that: The anti-collapse automobile interior genuine leather (10) comprises the following components arranged in order from top to bottom: Leather layer (11); Hot melt adhesive film layer (12); Mesh cloth layer (13); in, The mesh cloth layer (13) is a knitted fabric, the transverse elongation of the mesh cloth layer (13) is a, and the longitudinal elongation of the mesh cloth layer (13) is b, satisfying the quantitative relationship: a≠b.
2. The anti-collapse automotive interior genuine leather according to claim 1, characterized in that: The hot melt adhesive coating amount of the hot melt adhesive film layer (12) is 23±2 / g.
3. The anti-collapse automotive interior genuine leather according to claim 1, characterized in that: The thickness of the leather layer (11) is 1.2±2 mm.
4. The anti-collapse automobile interior genuine leather according to claim 1, characterized in that: The leather layer (11) is provided with through holes, the hole diameter of the through holes is 1.0 mm, and the hole spacing is 4*4 mm.
5. The anti-collapse automotive interior genuine leather according to claim 1, characterized in that: The leather layer (11) is a car interior vegetable tanned leather with a high bio-based carbon content.
6. The anti-collapse automobile interior genuine leather according to claim 5, characterized in that: The method for preparing vegetable tanned leather for automotive interior with high bio-based carbon content comprises the following preparation steps: Step 1: Water field process; Step 2: coating process; in, The water yard process includes: fur feeding, soaking, liming, splitting, deliming, pickling, tanning, retanning, dyeing, fatliquoring and finishing; The coating process includes: base coating, surface coating, and top coating; It is characterized in that The biomass material CoralonNL Liquire is used in the fur to white leather stage, and the biomass material accounts for 10 to 30 parts by weight; Biomass materials are used in the tanning stage, and the biomass materials account for 80 to 100 parts by weight; Biomass materials are used in the retanning stage, and the biomass materials account for 40 to 60 parts by weight; Biomass materials are used in the dyeing stage, and the weight proportion of the biomass materials is 0 to 10 parts; Biomass materials are used in the fatliquoring stage, and the biomass materials account for 20 to 70 parts by weight; Biomass materials are used in the coating stage, and the biomass materials account for 30 to 60 parts by weight.
7. A leather seat structure, characterized in that: Including settings from top to bottom: The anti-collapse genuine leather for automobile interior decoration (10) according to any one of claims 1 to 4; Leather composite sponge (20); Zero gravity filling layer (30).
8. The leather seat structure according to claim 5, characterized in that: The compressive strength of the zero-gravity filling layer (30) is 6.5±2.5 / Kpa.
9. The leather seat structure according to claim 5, characterized in that: The thickness of the leather composite layer sponge (20) is 8-10 mm.
10. The leather seat structure according to claim 5, characterized in that: The zero gravity filling layer (30) has a thickness of 10 to 15 mm.
Citation Information
Patent Citations
Anti-collapse automobile interior real leather
CN223545928U